Ionic liquid functionalized nano-zerovalent cerium for catalytic degradation of carbamazepine and colorimetric sensing of H2O2. (April 2021) - Shah, Noor S.; Iqbal, Jibran; Sayed, Murtaza; Rauf, Sajid; Albaqami, Munirah D.; Khan, Javed Ali; Khan, Zia Ul Haq; Rehman, Faiza; Khan, Ajmal; Naseem, Muhammad; Hashmi, Aleena Imtiaz
Graphical abstract: Highlights: Chemical reduction method successfully synthesized ionic liquid functionalized nZVCe. IL-nZVCe showed good performance in degradation of CBZ and detection of H2 O2 . IL-nZVCe catalyzed H2 O2 into ● OH that showed high reactivity with CBZ. High dose of IL-nZVCe and H2 O2 promoted removal of CBZ. Degradation products of CBZ as well as ecotoxities of CBZ and DPs were identified. Abstract: This study reported the chemical reduction method based synthesis of ionic liquid (IL) functionalized nano-zerovalent cerium (nZVCe) for the degradation of carbamazepine (CBZ) and colorimetric detection of H2 O2 . Carbamazepine is an important class of emerging water pollutants while H2 O2 is produced as a major by-product by living organisms during metabolism. The synthesized IL-nZVCe showed high efficiency towards CBZ degradation and H2 O2 detection. The use of advanced characterization techniques showed the prepared material to be highly crystalline and of high surface area, i.e., 85 m 2 /g. The IL-nZVCe caused 56% removal of CBZ, however, the use of H2 O2 and IL-nZVCe promoted the removal of CBZ to 85% under 80 min treatment time using [IL-nZVCe]0, [CBZ]0 and [H2 O2 ]0 as 0.5 g/L, 10 mg/L and 40 mg/L, respectively. IL-nZVCe/H2 O2 yielded ● OH which showed high reactivity of 5.40 × 10 9 (M s) –1 with CBZ and played active role in CBZ degradation. Removal of CBZ was inhibited in the presence of ● OH scavengers. The IL-nZVCe/H2 O2 –mediated removal of CBZ was promoted under the conditions of high [H2 O2 ]0, high [IL-nZVCe]0 and low [CBZ]0 . IL-nZVCe/H2 O2 was also highly effective in TOC removal of CBZ. The IL-nZVCe showed high reusability than nZVCe. The acute and chronic toxicities of CBZ degradation products identified by LC–MS analysis were estimated. The conversion of CBZ into non-toxic acetate suggests high potential of the IL-nZVCe/H2 O2 into remediation and detoxification of CBZ.